Low temperature oxygen diffusion mechanisms in Nd2NiO4+δ and Pr2NiO4+δvia large anharmonic displacements, explored by single crystal neutron diffraction. Issue 42 (25th September 2015) - Ceretti, M.; Wahyudi, O.; Cousson, A.; Villesuzanne, A.; Meven, M.; Pedersen, B.; Bassat, J. M.; Paulus, W.
Abstract : Quasi-continuous shallow energy diffusion pathway and anharmonic double potential of the apical oxygen atoms in Pr2 NiO4.25 explored by single crystal neutron scattering at 400 °C. Abstract : We investigated the structure of Nd2 NiO4+ δ and Pr2 NiO4+ δ by single crystal neutron diffraction studies. While the real structure of both compounds is incommensurate, the scattering density of the respective average structures was explored using the Maximum Entropy Method. Unusually high displacement factors were found for the equatorial and apical oxygen atoms showing respectively large displacement amplitudes towards [001] and [110] with respect to the F-symmetry cell. The shifts of the apical oxygen atoms reach up to 1 Å from their average position, corresponding to a 25° tilt of the NiO6 octahedra. At 400 °C, i.e. slightly above the orthorhombic-tetragonal phase transition, the anharmonic apical oxygen displacements towards [110] in the commensurate tetragonal parent structure are strongly enhanced, showing a double-well potential and pointing towards the interstitial vacancy sites, creating a quasi continuous shallow energy diffusion pathway between apical and interstitial oxygen sites. These large displacement amplitudes are considered to be – at least partially – of dynamical origin, which is consistent with a phonon assisted diffusion mechanism, already activated at very moderate temperatures.